Cultural Trauma in the Novel “Forest of The Gods” by Balys Sruoga - Bankauskaitė, Gabija; Andriukevičiūtė, Justina (Respectus Philologicus, 2018)
[full article and abstract in Lithuanian; abstract in English]The object of this research is cultural trauma. The signs of the cultural trauma are sought in the novel „Dievų miškas“ ("Forest of The Gods", 1957) by Balys Sruoga (1896–1947). The repressions of Nazis and cultural trauma that they caused is a new subject that did not get enough attention in the field of literature. Importance of this research is based on the idea that it is impossible to overcome the cultural trauma without consideration and discussion. The article defines the relation between text and context on the basis of the ideas of new historicism. The analysis is intended to reveal what traumatic events are represented in the novel and how the identity of the person reveals in the one, and how traumatic experience changes story style and structure.Analysis of the novel reveals that the characters face difficult living conditions, physical and psychological violence, and the constant fear of death; these things cause change of values. The irony was noticed in the novel. An ironic story becomes a language of traumatic experience that helps to avoid a sensitive story, disassociate from personal experience, and tell the tragedy of a nation. One must emphasize that in the story of traumatic experience flashbacks get very important. Finally, analysis reveals that in the novel by B. Sruoga the most important sign of identity is culture
Keywords: rauma, Culture, Novel, Balys Sruoga